Penguatan Branding Produk Pertanian Unggulan Melalui Integrasi Teknologi Solar tunnel dryer di BUMDes Tamanmartani - Victoria Sundari Handoko; Desideria Cempaka Wijaya Murti; Emerita Setyowati; Sesilia Eka Tri Astuti; Stephany Emmanuela Lesar; Gabriel Hacarya Adhi; Fridolin Satriya Indratma (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
The community service program at BUMDes Tamanmartani, Sleman Regency aims to strengthen the branding of leading agricultural products through the integration of Solar tunnel dryer technology. This collaboration is designed to enhance the capacity of BUMDes in managing local agricultural products, providing added value and improving their competitiveness in the market. Branding reinforcement is carried out by exploring the potential of village flagship products and developing marketing strategies based on innovative drying technology. The social entrepreneurship approach offers opportunities for villagers to collaborate, share knowledge, and optimize agricultural yields with improved quality. Problem-solving serves as the main method in addressing the challenges faced by BUMDes, including production management, marketing, and resource utilization. This is achieved through participatory discussions between the community service team, BUMDes administrators, and members of BUMDes. Furthermore, the program includes marketing training and the sustainable use of Solar tunnel dryer technology. Activities also cover the development of branding programs for agricultural products, the enhancement of BUMDes marketing skills, and the strengthening of distribution networks, enabling Tamanmartani’s agricultural products to compete at both local and regional levels.